Women and work in irrigated landscapes in rural India - Girard-Zdanowska, A; Alexandra M. Girard-Zdanowska (2014)
In India, the 1992 Reservation Law and the 2006 Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) have formalised women as legitimate actors in rural development. These gender-inclusive policies do not necessarily conform to the traditional domestic role of women, which often precludes them from formally engaging in political processes and labour outside the home. In Northern India, these major policy shifts are illustrated in ancient irrigation management systems. With growing rural outmigration and climatic variability aggravating water resources and food security issues, irrigation management is increasingly dependent on the active participation of women. Yet irrigation management is still widely perceived as a male responsibility. This thesis investigates how women adapt and respond to new institutionally mandated responsibilities and expectations as female leaders and as water users. The research is presented in four complementary papers based on quantitative and qualitative data collected during fieldwork in Delhi and Himachal Pradesh. Three major findings emerged to contribute to theories and evidence of the role of public policies in shaping gendered outcomes for common pool resource management in irrigation system in India. First, gender norms affect women differently depending on their public role in the community. Unlike non-political women, female leaders, as public figures, must secure communal approbation to gain power, credibility, and socio-economic networks. As a result, female leaders shape their political behaviour and policy preferences around local notions of femininity, female morality, and labour-based ideas of expertise. Second, for female water users, gender inclusive policies that legitimise their role as participants in formal political processes and the labour force for irrigation management increase their likelihood to defy gender-based restrictions and engage in formal political processes around irrigation management. Third, providing that formal/legal structures legitimize their actions, women will readily breach gender norms if they are to economically benefit from it. The implication of this research are that policies aimed at providing legal support for women to engage in formal rural development, combined with formalised economic opportunities for women are effective eroding agents of gendered institutions and are catalysts in facilitating the engagement of women in all areas of rural development. Given worldwide concerns over rural development, this study encourages such governmental actions to enable the effective and full engagement of future generations of women in the formal management of common pool resources.